Pengembangan E-Modul Peninggalan Sejarah Kolonialisme Inggris di Bengkulu Berbasis Discovery Learning pada Pembelajaran Tematik Terpadu Kelas V Sekolah Dasar - Nabila Khansa Putri; Pebrian Tarmizi (JURIDIKDAS, 2023)
This research was conducted to produce an integrated thematic learning E-Module based on discovery learning on the theme of 7 sub-themes 1 learning 1 & 2 in grade V elementary school. This type of research is Research and Development (R&D) with the model The development model used in this study is ADDIE. The instruments used are product validation sheets, teacher response questionnaires, and student response questionnaires. Data analysis techniques use qualitative descriptive analysis by processing data in the form of notes, suggestions or comments from expert validation, questionnaires for teacher and student responses and quantitative analysis by processing data in the form of scores from expert validation assessment results, teacher response questionnaires, and students. The material expert validation results showed a value of 92.9%, media expert validation showed a value of 97% with a very valid category and linguist validation showed a value of 93.3% with a very valid category. In addition, teacher responses showed a score of 93.7% and the trial results obtained a range of 0.7 with a moderate category, meaning that teaching materials are suitable for use and student responses showed a score of 89.63% with excellent categories that can be used in learning. The results of the overall assessment show that the E-Module of the historical relics of British colonialism in Bengkulu based on discovery learning is very feasible and effective to be used in learning.